Local subcutaneous lidocaine injection for the treatment of complex regional pain syndrome: a case report and literature review - Su, Yaping; Li, Zhenyu; Wang, Qian; Tang, Hui (Frontiers in Neurology, 2023)
A 14-year-old child was diagnosed with complex regional pain syndrome (CRPS) after bromhidrosis surgery. She experienced a stinging, knife-like, and intermittent attack pain, accompanied by numbness of both upper limbs and limited movements. Ultrasound-guided radiofrequency surgery on the peripheral nerve did not reduce pain. Then, gabapentin 300 mg three times a day and 2% lidocaine by local subcutaneous injection once a day for 3 days were administrated. After the local subcutaneous injection of lidocaine, the pain was significantly relieved, and the pain induced by skin touch at the scar disappeared. No pain recurred after the 1-month follow-up. An evidence-based literature review showed that local or systemic intravenous lidocaine was used to reduce adult CRPS symptoms but less has been reported in children. In our case, a local subcutaneous injection of 2% lidocaine in a child for CRPS treatment was reported to be effective in relieving complex local pain with favorable outcomes. Though further high-quality randomized controlled trials are needed to investigate the effects and safety of local subcutaneous lidocaine injection on pain relief in children with CRPS, it could still provide a relatively safe and effective adjuvant therapy for minor patients.